Taking a step further: Gender and fish value chains - Kruijssen, Froukje (International Livestock Research Institute, 2016)
Gender in value chain is increasingly receiving attention: lots of toolkits have been developed. The researchers wanted to take what as been developed a step further by using gender-transformative approaches to understand the dynamics and bring about lasting changes. Interview with Froukje Kruijssen (WorldFish) for the book "A different kettle of fish? Gender integration in livestock and fish research": http://hdl.handle.net/10568/76684